Path optimization using genetic algorithm evolution - Low C.Y.; Chong K.H.; Salleh K.; Johnny K.S.P. (2023)
Gantry robots are widely used in the industries for various material handling applications. The robot capable of moving in the Cartesian makes it very flexible and efficient at big or small areas. Path optimization to the robot would make it more efficient and easier automation. In this paper, genetic algorithm (GA) has been proposed to optimize the traveling sequence making the movement more efficient and economic as the total travel length is shortened. 2010 IEEE.